Adolescent alcohol use: a reflection of national drinking patterns and policy?. (5th August 2014) - Bendtsen, Pernille; Damsgaard, Mogens Trab; Huckle, Taisia; Casswell, Sally; Kuntsche, Emmanuel; Arnold, Petra; de Looze, Margreet E.; Hofmann, Felix; Hublet, Anne; Simons‐Morton, Bruce; ter Bogt, Tom; Holstein, Bjørn E.
Abstract Aims To analyse how adolescent drunkenness and frequency of drinking were associated with adult drinking patterns and alcohol control policies. Design, Setting and Participants Cross‐sectional survey data on 13‐ and 15‐year‐olds in 37 countries who participated in the Health Behaviour in School‐Aged Children (HBSC) Study in 2010 (n = 144 788) were linked to national‐level indicators on alcohol control policies and adult drinking patterns. Measurements Outcome measures were self‐reported weekly drinking and life‐time drunkenness (drunk once or more). Data were analysed using multi‐level logistic regression models. Findings In the mutually adjusted models, adolescent drunkenness was associated significantly with high adult alcohol consumption [odds ratio (OR) = 3.15 among boys, 95% confidence interval (CI) = 2.13–4.64, OR girls = 2.44, CI = 1.57–3.80] and risky drinking patterns in the adult population (OR boys = 2.02, CI = 1.33–3.05, OR girls = 1.61, CI = 1.18–2.18). The level of abstainers in the adult population was also associated significantly with girls' drunkenness; a 10% increase in the number of abstainers in a country reduced the odds of drunkenness with 21% (OR = 0.79, CI = 0.68–0.90). Weekly drinking was associated significantly with weak restrictions on availability (OR boys = 2.82, CI = 1.74–4.54, OR girls = 2.00, CI = 1.15–3.46) and advertising (OR boys = 1.56, CI = 1.02–2.40, OR girls = 1.79, CI = 1.10–2.94). Conclusions Comparing data cross‐nationally, high levels of adult alcohol consumption and limited alcohol control policies are associated with high levels of alcohol use among adolescents.